2011
DOI: 10.1071/mf10105
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting population genetic structure of two widespread aquatic insects in the Chilean high-slope rivers

Abstract: Dispersal and many other factors affect population genetic structure. In central Chile, rivers are characterised by strong currents and transverse mountain chains, which impose physical barriers to the populations that inhabit them. The objective of the present study was to study the population genetic structure of two widespread species of aquatic insects, the caddisfly Smicridea annulicornis and the mayfly Andesiops torrens, in three isolated rivers, Choapa, Maipo and Maule. The analysis of population struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…Sabando et al . (), on the other hand, observed low dispersal rates and low connectivity between sites for one caddisfly species in South America, suggesting that patterns are likely to be species specific. This is not surprising considering different morphological constitutions and life‐history traits relevant for dispersal (e.g.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Sabando et al . (), on the other hand, observed low dispersal rates and low connectivity between sites for one caddisfly species in South America, suggesting that patterns are likely to be species specific. This is not surprising considering different morphological constitutions and life‐history traits relevant for dispersal (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Previous population genetic studies of headwater insect species have mainly used DNA sequencing and AFLPs to assess regional patterns and revealed strong catchment differentiation (e.g. Hughes et al ., ; Wishart & Hughes, ; Lehrian et al ., ; Yaegashi et al ., ), strong differentiation within catchments (Monaghan et al ., ) or variation among codistributed taxa (Monaghan et al ., ; Sabando et al ., ). A few examples also show effective dispersal with limited population structure (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, flying species might overcome geographical barriers more readily (Townsend et al ., ). The ability of some flying taxa (mayflies) to disperse between river basins is supported by population genetic data from a study in north‐central Chile spanning one of the basins included here (Sabando et al ., ). In our study, the importance of flight in structuring the flying assemblage is suggested by the fact that the majority of the taxa with spatially structured abundance preferentially dispersed via active flight (Verdugo, ), and their greater dispersal aptitude is substantiated by the broad‐scale spatial pattern that we detected for this group.…”
Section: Discussionmentioning
confidence: 99%
“…Partly, however, the different resolution might also be explained by the different biology as well: the low dispersal capacity of land snails usually leads to stronger population differentiation than can be generally expected from flying insects. However, studies of winged aquatic insects have shown species-specific patterns of genetic population structure and population differentiation that suggest dispersal capacity varies dramatically even among ecological similar or closely related species [28,69,70], which is also true for land snails e.g. [71].…”
Section: Discussionmentioning
confidence: 99%
“…However, the large geographic overlap and co-occurrence of only slightly disjunct clades at the same sites argues against a deeper biological significance of the inference clade level. In other species of Smicridea population structure and population differentiation are more pronounced, even at smaller geographic scales [42,70]. In Trochulus , highly divergent and reproductively isolated lineages may be restricted to single valleys [36,72,73].…”
Section: Discussionmentioning
confidence: 99%